2020
DOI: 10.3390/antiox9080662
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of HIF Prolyl Hydroxylase Inhibition in an In Vitro Hypoxia Model

Abstract: A novel potent analog of the branched tail oxyquinoline group of hypoxia-inducible factor (HIF) prolyl hydroxylase inhibitors, neuradapt, has been studied in two treatment regimes in an in vitro hypoxia model on murine primary hippocampal cultures. Neuradapt activates the expression of HIF1 and HIF2 target genes and shows no toxicity up to 20 μM, which is more than an order of magnitude higher than its biologically active concentration. Cell viability, functional activity, and network connectivity between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 67 publications
0
28
0
Order By: Relevance
“…The spontaneous calcium activity of primary hippocampal cultures was recorded on day 7 post-ischemic damage. The following main parameters were analyzed: duration of calcium events (time period from the beginning to the end of an oscillation, s), frequency of calcium oscillations (average number of oscillations per min), and percentage of active cells (the cells number with at least one recorded oscillation divided by the total cell number, %) [ 18 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The spontaneous calcium activity of primary hippocampal cultures was recorded on day 7 post-ischemic damage. The following main parameters were analyzed: duration of calcium events (time period from the beginning to the end of an oscillation, s), frequency of calcium oscillations (average number of oscillations per min), and percentage of active cells (the cells number with at least one recorded oscillation divided by the total cell number, %) [ 18 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…A 100% value characterizes the maximally possible level of significant correlations in the network. An increase in the last two parameters considered above indicates the presence of a long-term significantly correlated response of the cell network, whereas their low levels characterize its absence [ 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoxia is one of the most common experimental models of brain cell damage [ 18 ]. Several studies have shown a significant decrease in the viability and functional activity of brain cells in models of 10-min acute hypoxia in vitro [ 18 , 19 , 20 ]. However, astrocytes are considered more resistant to hypoxic damage than neurons.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies addressed the changes in the functional activity of neuronal networks in hypoxic and ischemic lesions. Earlier, we demonstrated that hypoxia leads to the dramatic suppression of network interactions between neural cells, up to complete disruption, that is manifested in the alterations of both the calcium and bioelectric activity, as recorded by multi-electrode matrices [ 19 , 20 ]. At the same time, little is known regarding the network activity of mono-astrocytic cultures.…”
Section: Discussionmentioning
confidence: 99%